The relationship between brand Facebook page characteristics, perceived value, and customer engagement behavior: An application of Stimulus-Organism-Response (S-O-R) - Aslam, Wajeeha; Luna, Iviane Ramos de (Review of Business Management, 2021)
Purpose – With the advancement of technology and increased use of social media, brands have become part of the virtual world and try to grab customers’ attention. Brand pages enable the consumer to voluntarily participate in providing feedback and ideas and to collaborate with others. This adds value to the firm. This research explores which characteristics help clothing brands to influence consumers into responding in the form of feedback, collaboration, and mobilization. Design/methodology/approach – Data were collected from 250 respondents who had purchased their favorite clothing brand in the last four months, using five-point Likert scale questionnaires. Partial least squares structural equation modeling (PLS-SEM) was used to analyze the data. Findings – The results indicate that content quality leads to brand learning values and hedonic values. Customer contact quality only affects brand learning value. Both hedonic and brand learning values induce customer engagement behaviors. Originality/value – This study provides useful insights for clothing brand webpage managers related to customer engagement in social media. The study extends the concept of customer engagement behavior (CEB) by incorporating consumer “mobilizing behavior” as an additional element of CEB.